2020
DOI: 10.7717/peerj.10396
|View full text |Cite
|
Sign up to set email alerts
|

Driver versus navigator causation in biology: the case of insulin and fasting glucose

Abstract: Background In biomedicine, inferring causal relation from experimental intervention or perturbation is believed to be a more reliable approach than inferring causation from cross-sectional correlation. However, we point out here that even in interventional inference there are logical traps. In homeostatic systems, causality in a steady state can be qualitatively different from that in a perturbed state. On a broader scale there is a need to differentiate driver causality from navigator causality. A driver is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 145 publications
0
24
0
Order By: Relevance
“…The question whether tight glycemic control leads to subtle neuronal changes in the long run as expected by our model needs careful investigation. The difference between fasting and post meal regression correlation parameters between glucose and insulin is an important epidemiological line of evidence we have used.Chawla et al (2017) and Diwekar-Joshi andWatve (2020) showed this pattern across four different data sets. How generalized the pattern is can be easily tested in multiple populations.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…The question whether tight glycemic control leads to subtle neuronal changes in the long run as expected by our model needs careful investigation. The difference between fasting and post meal regression correlation parameters between glucose and insulin is an important epidemiological line of evidence we have used.Chawla et al (2017) and Diwekar-Joshi andWatve (2020) showed this pattern across four different data sets. How generalized the pattern is can be easily tested in multiple populations.…”
mentioning
confidence: 70%
“…By classical models the regression correlation parameters of glucose-insulin relationship are not different in fasting state versus post glucose load although the range of variables is different as shown previously by Diwekar-Joshi andWatve (2020). Also, if we assume HOMA-IR to faithfully reflect insulin resistance and HOMA β to faithfully represent β cell response, then there is no reason why the two indices should be correlated.The assumption behind our model that there are different mechanisms at work under fasting versus post glucose load condition is necessary to explain the large difference in the regression correlation parameters in fasting versus post meal levels.…”
mentioning
confidence: 79%
See 3 more Smart Citations